Association Between Soluble CD14 in the Aqueous Humor and Hyperreflective Foci on Optical Coherence Tomography in Patients With Diabetic Macular Edema - Lee, Hyungwoo; Jang, Hyoik; Choi, Youn A; Kim, Hyung Chan; Chung, Hyewon (Investigative ophthalmology & visual science, 2018)
To investigate the associations between soluble CD14 (sCD14), a cytokine released by microglia and macrophages, and hyperreflective foci (HF) and various characteristics of spectral-domain optical coherence tomography (SD-OCT) in diabetic macular edema (DME). Sixty-nine eyes from 51 patients with DME and 28 eyes from 28 control subjects were studied. sCD14 levels in the aqueous humor (AH) were measured using ELISA before bevacizumab injection (IVB), and the associations between sCD14 and visual acuity, the number of HF, retinal volume, and the DME pattern were assessed. sCD14 levels were higher in DME patients than in the control subjects (29.9 ± 41.6 pg/mL versus 8.1 ± 3.6 pg/mL, P < 0.001). sCD14 levels in diffuse edema were higher than those in focal edema (50.0 ± 65.3 pg/mL versus 19.8 ± 14.7 pg/mL, P = 0.039). The number of HF in the inner retina of patients with diffuse edema was significantly higher than that in patients with focal edema (4.4 ± 2.3 vs. 2.6 ± 2.1, P = 0.001), but no difference was found in the outer retina (5.8 ± 3.4 vs. 5.0 ± 3.9, P = 0.25). According to multivariate analyses, elevated sCD14 levels were associated with an increased inner nuclear layer volume and the total number of HF in all retinal layers on SD-OCT. Reduction of DME following IVB was correlated with reduction in the number of HF in a subset of eyes followed longitudinally in the study (n = 30). DME patients with diffuse edema exhibit higher sCD14 levels in the AH and more HF in the inner retina than patients with focal edema, indicating severe inflammation. The strong correlation between sCD14 and HF in the inner retina suggests that the HF observed on SD-OCT may be due to activated microglia in DME.